Development of Solar Maximum Power Point Tracking Algorithm for Multiple Angle Condition - Samsul Bahri, M. Hanif Aiman; Yahaya, Jabbar Al-Fattah (Evolution in Electrical and Electronic Engineering, 2023)
Due to its clean and limitless nature, photovoltaic (PV) energy is one of the most significant energy sources. However, low energy conversion efficiency and high installation costs are two drawbacks of PV or solar panels. The improved efficiency of PV can be obtained by attempting to make the panel run at its maximum power point (MPP). It is also the objective of this work to compare the performance between Perturb & Observe (P&O) algorithm and Incremental Conductance (InC) algorithm for multiple angle conditions. This work used P&O and InC algorithms as the system in the MPPT. The angle of the solar panel has manually been adjusted. Boost converter work be act as the MPPT structure while the algorithm would be run using Arduino. The angle has been used in the indoor practical. The indoor experiment was run because of outdoor conditions that were unstable within the period of run testing. All situation shows that both systems work properly by increasing the output voltage the average output power when using the P&O algorithm are higher than when using the InC algorithm. The average output power at and for P&O was higher than InC while at is slightly lower than InC. From the result, it could be concluded that the P&O algorithm gives a higher average output power than the InC algorithm. This happens because of time used for InC to reach the nominal peak is longer than P&O. For future work, a microcontroller to control the tilt angle with the aid of a motor while also doing this at the outdoor condition with having 2 prototypes to both each algorithm simultaneously.